Analisis Peran Social Media Marketing dan Kualitas Produk Terhadap Keputusan Pembelian pada Ayam Bakar Pak D Surabaya - Meilia Dwi Maulani; Zumrotul Fitriyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the effect of social media marketing and product quality on purchasing decisions with a case study of consumers at Ayam Bakar Pak D Surabaya, Rungkut Madya Branch. The method used in this study is a quantitative method, with data analysis using the component-based SEM method with the Partial Least Square (PLS) approach. The sample in this study was taken using a non-probability sampling method with an accidental sampling technique or incidental sampling technique. The questionnaire was distributed via Google Form and distributed to 91 respondents who had purchased products from Ayam Bakar Pak D Surabaya, Rungkut Madya Branch. The results of the study indicate that social media marketing has a positive effect on purchasing decisions. In addition, product quality also has a positive effect on purchasing decisions.